Pharmacokinetic evaluation and In Vitro–In Vivo Correlation (IVIVC) of novel methylene-substituted 3,3′ diindolylmethane (DIM) - Patel, Apurva R (2012)
PURPOSE: 3,3′-Diindolylmethane (DIM) is the major in vivo product of the acid-catalyzed oligomerization of indole-3-carbinol present in cruciferous vegetables. 1, 1-bis (3′-indolyl)-1-(p-substituted phenyl) methanes [C-substituted diindolylmethanes (C-DIMs)] are a new class of anticancer compounds derived from indole 3-carbinol. Despite rapidly increasing knowledge regarding mechanisms responsible for the chemopreventive properties of DIM-C-pPhC(6)H(5), there have been relatively few studies determining the absorption and pharmacokinetic properties of DIM-C-pPhC(6)H(5) to explore its clinical utility. METHODS: In this study, we assessed the solubility, lipophilicity and Caco-2 cell permeability of methylene-substituted DIM. Pharmacokinetic properties in rats were determined following i.v. and oral administration of a novel analog of DIM. Pharmacokinetic parameters were determined using noncompartmental and compartmental techniques with WinNonlin® 5.0 software. To explore potential In Vitro–In Vivo Correlation (IVIVC) between the in vitro permeability values, and the oral absorption pharmacokinetics, we employed deconvolution of i.v. and oral data using a three compartment Exact Loo–Riegelman method. RESULTS: The oral absorption and disposition were described by a three compartment model with combined zero-order/Michaelis–Menten limited systemic uptake using differential equations, at physiologically relevant doses. The saturation model obtained accounts for a nonlinear change in C(max)/Dose, and the absolute bioavailability (0.13 ± 0.06) was also dose dependent. The absorption rate profile of DIMC-pPhC(6)H(5) across Caco-2 cells was significantly different than in vivo. Conclusions: The pharmacokinetic absorption model presented represents a useful basis for obtaining plasma level predictability for poorly bioavailable, highly lipophilic drugs, such as the DIM analog DIM-C-pPhC(6)H(5).